2019
DOI: 10.11646/phytotaxa.397.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogeny and morphology of Alternaria reveal a novel species and a new record in China

Abstract: Two Alternaria species, A. carotiincultae and A. glehniae sp. nov. are isolated from necrotic leaf symptoms of Ligusticum chuanxiong Hort. and Glehnia littoralis Fr. Schmidt ex Miq in China, respectively. The two species are determined as distinct species belonging to sect. Radicina of Alternaria based on morphology and a multigene analysis of ITS, EF-1α, RPB2 and ATPase sequences. Alternaria glehniae is illustrated here as a novel species because the conidial size, septa and sporulation patterns are different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Recent diagnosis techniques e.g., PCR is more reliable for pathogen detection (Khan et al 2018). The ribosomal genes and their ITS regions have been extensively used for distinguishing and naming of the species (Yang et al 2020), along with the study of genetic diversity (Ghosh et al 2019;Turzhanova et al 2020), phylogenetic relationship (Ozkilinc et al 2018;Liu et al 2019;Tao et al 2019), and taxonomic studies (Mahmoudi et al 2017;Poursafar et al 2018). In fungi, ITS region is used in species identification and phylogenetic studies of closely related species (Mmbaga et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent diagnosis techniques e.g., PCR is more reliable for pathogen detection (Khan et al 2018). The ribosomal genes and their ITS regions have been extensively used for distinguishing and naming of the species (Yang et al 2020), along with the study of genetic diversity (Ghosh et al 2019;Turzhanova et al 2020), phylogenetic relationship (Ozkilinc et al 2018;Liu et al 2019;Tao et al 2019), and taxonomic studies (Mahmoudi et al 2017;Poursafar et al 2018). In fungi, ITS region is used in species identification and phylogenetic studies of closely related species (Mmbaga et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Except for A. atrocariis, which had no published sequence data, the two other species were shown to belong to other sections: A. japonica felled in the section Japonicae and A. soliaridae formed a separate monophyletic lineage (Woudenberg et al 2013). Recently, two more species A. chlamydosporifera and A. glehniae were reported in the section Radicina (Marin-Felix et al 2019;Tao et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary BLAST searches in GenBank with ITS and TEF1 sequences of the present isolates indicated that they had a close phylogenetic relationship with species from section Radicina of Alternaria. Subsequently, sequence data of 19 Alternaria species and Stemphylium herbarum CBS 191.86 (outgroup) were retrieved from National Center for Biotechnology Information (NCBI), mostly published in Marin-Felix et al (2019), Woudenberg et al (2013), andTao et al (2019) (Table 1). The gene sequences were concatenated and edited manually according to ITS+TEF1+GAPDH+RPB2 for YZU 161234 and YZU 161235 and ITS+TEF1+RPB2 for YZU 151055 and YZU 151059 with equal weight in MEGA v.7.0.26 (Kumar et al 2016).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations